Irish mobilities - WICKHAM, JAMES JOHN RUFUS (UCD Press, 2007)
The `mobility turn? in sociology challenges our easy equation of `society? with a given territorial area. The chapter begins by examining the arguments involved, pointing out how much sociological theorising about `fluidity? (e.g. Bauman) shares common assumptions with the extreme free market globalisation writers (e.g. Freeman). Using arguments from the sociology of technology, it is argued that we need to examine how new mobilities are created and also constrained, the uses that actors make of them and the consequences of such usage. This approach allows us to link the study of migration with the study of other forms of mobility, to examine the origins of mobility within social structure and the impact of mobility on social structure. The chapter then briefly reviews the extent to which conventional indicators show an expansion of mobility within and to/from Ireland: personal car ownership, air travel, migration. Against this background it discusses four different examples of mobility. A) Constrained mobility - car dependency in Dublin Rising car ownership in the Dublin area is linked to new constraints on mobility, from lengthening journey times for car users to the increasing marginalisation of those without cars. Our comparisons with some other cities shows that while this is hardly unique to Dublin, it is linked to the particular political governance of the city. B) Mobile careers ? software immigrants in Ireland The Celtic Tiger boom has depended on the immigration of large numbers of software workers, facilitated by ubiquitous air travel, internet-based job advertising and a global occupational mobility. However, such mobility has been generated by the very specific nature of the Irish software industry, in particular the reluctance of Irish firms to develop training. It does not occur in a boundaryless space, since it is shaped by national state regulation of migration. Equally, while individuals have used opportunities to travel to Ireland, our interviews show how their decisions are constrained by life cycle and family context, as well as by the labour market and training opportunities. . 3. Mobile lives ? travelling software workers Our study of business travel within the Irish software industry shows how high levels of business travel (which shades into migration) are also generated by particular features of the industry: its orientation to the US market and the way in which the very importance of a software `cluster? in Dublin also makes important `pipes? which connect the cluster to other clusters. Paradoxically the high usage of various forms of electronic communication within the industry also makes business travel even more important in order to maintain the `co-presence? on which effective ICT use depends. 4. Mobile assets ? Irish second homes abroad Flights from Central Europe are full of migrants coming to work in Ireland ? and Irish people (including people from the software industry) who have purchased property in these same countries. Such mobility is facilitated by the expansion of different forms of markets - cheap air travel as pioneered by Ryanair, the creation of markets for housing across Europe, the end of exchange controls, easy electronic funds transfer. Such mobility impacts back on social structure: it creates new forms of inequality for some while loosening the link between occupation and life chances for others.
PUBLISHED
Keywords: mobilities; transport